Linear and Non-Linear Population Retrieval with Femtosecond Optical Pumping of Molecular Crystals for the Generalised Uniaxial and Biaxial Systems - Christopher D. M. Hutchison; Alisia Fadini; Jasper J. van Thor (Applied Sciences, 2022)
Femtosecond optical measurements of photoexcitable molecular crystals carry ultrafast dynamics information with structural sensitivity. The creation and detection of transient dynamics depend on the optical parameters, as well as the explicit molecular structure, crystal symmetry, crystal orientation, polarisation of the photoexciting beam, and interaction geometry. In order to retrieve the linear and non-linear population transfer in photoexcited crystals, excitation theory is combined here with the calculation of birefringence decomposition and is shown for both the generalised uniaxial and biaxial systems. A computational tool was constructed based on this treatment to allow modelling of electric field decomposition, dipole projections, and non-linear excitation population levels. This is available open source and with a GUI for ease of use. Such work has applications in two areas of ultrafast science: multidimensional optical crystallography and femtosecond time-resolved X-ray crystallography.